KOMPREHENSI PSIKOSOSIOSEMANTIK NAMA DIRI MAHASISWA IAIN SURAKARTA - Irwan Rohardiyanto (Tarling : Journal of Language Education, 2019)
There is consideration by most parents in giving proper names for their childrensuch as for expectation or praying. They use language varieties in supportingtheir expectations. This study Psychosociosemantically aims to elaborate propernames of IAIN (The State Islamic Institute) Surakarta. The problems of this studyare how are Psychosociosemantically the comprehension and reasons of givingthe proper names? And how are the formation of proper names? The method is a descriptive qualitative study. The writer conducts some descriptions in collecting the data, analyzing the data and getting some conclusions. The result of thestudy informs that in creating the proper names especially for students of IAINSurakarta, there is certain expectation and reason. Proper name is adopted fromthe name of certain people or character and created from certain event. Besides, itis also created from certain time (temporal) and certain place (spatial). The writerconcludes also that proper names are inspired from literary works title (especiallysongs title), kinds of profession, birth sequence, certain word formation, andfamily names. The forming of IAIN Students’ proper name is based on many ways,such as: formed from parents name combination, formed from father’s name,formed from mother’s name and formed from specific acronym.